Kontinuitás és diszkontinuitás az értékpreferenciákban (1977-1998) (Szociológiai Szemle, 2024)
The central assertion this paper wants to test is that communism exerted a very susbstantive and lasting, though mostly indirect, latent, hidden impact on society, and on value preferences. This claim can first be translated into two negative claims. One is that there was no comprehensive and basic reversal at the level o f individual value preferences towards the elimination of the fundamental difference with respect to the pattern exhibited by the 1968 American values. Some of the outstanding peculiarities of the value preferences o f Hungary as manifested in the late 1970s would therefore persist in the mid-1990s as well. The other assertion, however, is that there were nevertheless significant dislocations at the level of value preferences as compared to the communist period, refuting any substantive continuity, especially in so far as the most exposed socialist or communist values are concerned. These claims in themselves only assert a combination of continuities and discontinuities before and after 1989 that in itself would be a fairly trivial idea. They will therefore be complemented with a second set of more positive general hypotheses. They will be related to the clarification o f the distinction between direct vs. Indirect, or manifest vs. Latent differences. First, it will be argued that changes will be greater concerning the terminal than the instrumental values. Terminal values are explicity stated life-goals, while instrumental values are related to the modality of action and behaviour. Terminal values have a higher degree of visibility and immediacy, are closer to the surface of consciousness, while instrumental values are closer to ingrained habits, the modality of the conduct of life or the habitus. It will therefore be assumed that 1989 would hardly represent a major dislocation concerning the instrumental values, while there would be much more basic changes in the average preference of terminal values.